Autonomic testing - Novak, Peter (Neurologist) ([New York] : Oxford University Press, 2019)
Autonomic testing is an important addition to neurological evaluations. While there are many excellent textbooks on autonomic disorders, only a few texts focus on how to perform and interpret autonomic tests. This manual fills the gap, dealing mainly with the practical aspects of autonomic testing. In accord with the maxim that'a good picture is worth a thousand words,' signal drawings are heavily used throughout the text to explain and illuminate test results.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 8, 2019).
Keywords: Autonomic nervous system -- Diseases -- Diagnosis